2022
DOI: 10.3390/pathogens11080828
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils, but Not Type 2 Innate Lymphoid Cells, Are the Predominant Source of Interleukin 4 during the Innate Phase of Leishmania major Infection

Abstract: Interleukin (IL)-4 plays a central role in the initiation of a type 2 T helper cell (Th2) response, which leads to non-healing and progressive infections with the protozoan parasite Leishmania (L.) major. Here, we tested the hypothesis that type 2 innate lymphoid cells (ILC2), which promote the development of Th2 cells, form an important source of IL-4 early after intradermal or subcutaneous L. major infection. Lineage-marker negative CD90.2+CD127+PD1− ILC2 were readily detectable in the ear or foot skin, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…4 Upon infection, innate immune cells such as neutrophils monocytes and NK cells are activated in an attempt to control infection and instruct an adaptive response. 6,7 IFNγ derived from NKs, cytotoxic CD8 T cells and CD4 Th1 cells is fundamental to activate a respiratory program with nitric oxide (NO) species in infected macrophages. 8,9 In this inflammatory context, regulatory T cells (Tregs) are necessary to regulate the immune response by diverse mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Upon infection, innate immune cells such as neutrophils monocytes and NK cells are activated in an attempt to control infection and instruct an adaptive response. 6,7 IFNγ derived from NKs, cytotoxic CD8 T cells and CD4 Th1 cells is fundamental to activate a respiratory program with nitric oxide (NO) species in infected macrophages. 8,9 In this inflammatory context, regulatory T cells (Tregs) are necessary to regulate the immune response by diverse mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Host's intrinsic immunological factors are key to determine the clinical presentation of the disease 4 . Upon infection, innate immune cells such as neutrophils monocytes and NK cells are activated in an attempt to control infection and instruct an adaptive response 6,7 . IFNγ derived from NKs, cytotoxic CD8 T cells and CD4 Th1 cells is fundamental to activate a respiratory program with nitric oxide (NO) species in infected macrophages 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current studies, targeting IL-5 + ILC2s for deletion in the R5 : ROSA26iDTR or R5 : Gata f/f mice led to the reduced number of eosinophils, with downstream effects on the number of dermal TRMs due to the loss of a critical source of IL-4 required for their maintenance. A recent report confirmed eosinophils as the main intra-lesional source of IL-4 in L. major infected, C57BL/6 mice 39 . Evidence that IL-4/13 from eosinophils contributed to the upregulation of Tslp expression in dermal TRMs was provided by the scRNA-seq comparisons of relative Tslp expression within the dermal TRM cluster from infected, wild type and eoCre : IL4/13 f/f mice.…”
Section: Discussionmentioning
confidence: 77%
“…Despite the ILC2 predominance, in mouse skin lesions caused by L. major infection, it has been shown that eosinophils, rather than ILC2 cells, were the main source of IL-4 during the early stages of the disease [69]. IL-4 is a crucial factor in the expansion and differentiation of Th2 cells, which are critical for inducing alternative macrophage polarization.…”
Section: Ilcsmentioning
confidence: 99%